Examining the social support network in people with depressive disorder regarding age: differences between adolescent and adult patients - Munjiza Jovanovic, Ana; Krunic, Ana; Kostic, Milutin; Milenkovic, Danica; Ljajic, Lamija (Medical Research, 2025)
Introduction: Loneliness, isolation, and social support networks have routinely been shown to have a positive correlation with depressive disorder, but have not been sufficiently researched in different age groups. This study aimed to examine social network support in depressed patients and explore the association between social networks in adolescents and adults with depressive disorders. Material and Methods: The cross-sectional study was conducted, including 101 hospitalized patients: 47 adolescents and 54 adult patients. The examinees completed two questionnaires: the Beck Depression Inventory (BDI) and the Lubben Social Network Scale (LSNS-6). Results: There were no statistically significant differences between adults and adolescents in socio-demographic characteristics, except partnership status and household members, where adults lived with significantly fewer family members. Most patients (63.4%) were at risk of social isolation. A statistically significant moderate negative correlation was established between depression scores measured by the BDI and the Lubben Social Network Scale results and the family subscale scores in an adult patient sample. The severity of depression, as expressed through BDI scores, was not correlated with social support network results in adolescents. Conclusion: There is an association between depression in adulthood and the lack of family support, as well as the lack of a broader social support network, compared to depression in the younger, adolescent population. By understanding the intricacies of social support, we can more effectively predict and enhance the well-being of individuals.